Classroom Project: A Proposal Towards Teaching and Professional Development Innovation - María del Rosario Landín Miranda (Pontificia Universidad Católica del Perú, 2015)
An institutional policy that has generated collective work in the field of teacher's practice innovation and the training processes at the Universidad Veracruzana, Mexico, is the one called Aula Project (where Aula means Classroom). This project is a proposal based on three main axis: complex thinking; research and ICT. Inthe current document, I present an synthesis meta-reflexive originated from my experience in the implementation of the aforementioned project.